TANFĪŻU ISTIRĀTĪJIYYATI TALKING STICK LI TARQIYATI NATĀIJI ANSYIṬATI TA’LĪMI AL-LUGATI AL-`ARABIYYATI BI AL-MADRASATI ATSĀNAWIYYAH - M. Pd., Dedi Mulyanto; Attasyriki, Adam Fattullah; Binti Mahadi, Aina Dania Syahira (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2024)
This class action research was motivated by the low learning scores of 7-C students at MTsN 1 Ponorogo in Arabic subjects in recent years, especially in 2022. This is caused by students lack of concern for friends who are difficult to understand lessons, lack of innovation of teachers who only use the lecture method, which causes students to become bored and bored so that the learning process does not achieve learning targets and objectives. The purpose of this study is to explain the increase in learning activity and improvement of learning outcomes of grade 7-C students at MTsN 1 Ponorogo in Arabic subject. This type of research is Classroom Action Research. PTK or also called classroom action research with the type of collaborative action research PTK. In this study, researchers as teaching teachers and assisted by a supervisory teacher as an observer who supervises the condition of students. This research consists of two cycles, each cycle consists of: planning, implementation, observation, and reflection. Data collection techniques and tools in this study are using observation sheets and test results. The results showed that the Talking Stick learning model influenced cooperation between students in Arabic subjects. Student cooperation in the first cycle reached 42.68% and in the second cycle increased to 74.64%. The increase that occurred from the first cycle to the second cycle was 31.96%. In the learning outcomes of the first cycle of students, students who have reached KKM as many as 10 students, and students who have not reached KKM as many as 18 students, therefore researchers decided to carry out the second cycle. In the second cycle of students who have reached KKM as many as 23 students, while students who have not reached KKM as many as 5 students, with a percentage of completeness of 89%, from the results of the data above it can be concluded that the Talking Stick learning model can improve student cooperation and learning outcomes.